The impact of green consumption values on consumer attitudes and preferences for sustainable housing features in Singapore - Leong, Weng Sum (2025)
This thesis investigates how Green Consumption Values (GCV) shape consumer preferences and adoption intentions for sustainable housing features in Singapore. Recognising housing as a high-cost, high-involvement decision, the study examines the psychological mechanisms and contextual factors that influence the translation of environmental values into behavioural intention. A conceptual framework grounded in an extended Theory of Planned Behaviour (TPB) guides the analysis, incorporating additional constructs such as attitudes, perceived knowledge, symbolic value, willingness to pay (WTP), and perceived economic barriers.